What makes a frontal area of primate brain the frontal eye field? - Percheron, Gérard; François, Chantal; Pouget, Pierre (Frontiers in Integrative Neuroscience, 2015)
The frontal eye field region (FEF) of the oculomotor pathways has been intensely studied. The primary goal of this review is to illustrate the phylogenetic displacement of the FEF locus in primate species. The locus is arrayed along the arcuate sulcus in monkeys and abuts into the primary motor strip region in humans. The strengths and limitations of the various functional, anatomical and histological methodologies used to identify such regions are also discussed.